URGENSINYA PERAN SERTA POLRI TERHADAP PEMUSNAHAN BARANG BUKTI NARKOTIKA PADA TINGKAT PENYIDIKAN MAUPUN SETELAH PUTUSAN PENGADILAN NEGERI MEMPUNYAI KEKUATAN HUKUM TETAP ( INKRACHT VAN GEWIJSDE ) - Chandra cristian Gultom (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
Abstract The role of police on the implementation of the destruction of evidence of narcotics can be divided into two parts, namely the role of the police to the destruction of evidence in narcotics investigation conducted at the level and role of the police to the destruction of evidence after the verdict was legally binding (in Kracht van gewijsde). Constraints faced by the police in the execution of the destruction of drug evidence was given that the time available in the case of destruction of evidence in the investigation of narcotics at levels within only 24 hours since found it in a very short time it is quite difficult to police investigators were able to attend officials from relevant agencies as a witness in the event of destruction. Although officials from relevant agencies is actually present, specific to areas of conflict such as Aceh, for example, they rarely want to come because of some security reasons. Being the destruction of evidence nakotika can also pose problems in the implementation. This is due to the Narcotics Act does not regulate siting destruction of evidence of narcotics. In the case of evidence of narcotics destroyed in the level of investigation, the Narcotics Act does not specify how much should be set aside for the purposes of investigation, prosecution and examination in court, so it's a bit much to confuse investigators and police. Though police investigators is the most responsible of how the existence of evidence that narcotics should be set aside. Required considerable expense when the destruction of evidence of narcotics after the judge's decision is legally binding is done individually for each particular drug.